Padre Joaquin Garcia - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1984)
SPANISH: La fotografía muestra al padre Joaquin Garcia aun grupo de personas y autoridades regionales, en donde el padre muestra diferentes biblias
ENGLISH: The photograph shows Father Joaquin Garcia with a group of people and regional authorities, where he shows different bibles.

SPANISH: La fotografía muestra al padre Joaquin Garcia aun grupo de personas y autoridades regionales, en donde el padre muestra diferentes biblias
ENGLISH: The photograph shows Father Joaquin Garcia with a group of people and regional authorities, where he shows different bibles.
Father Joaquin Garcia
Keywords: S/N